Kinetic Modelling of Solid-Liquid Extraction of Tin From Dimethyltin Dichloride by-Products: Effect of Solvent and Stirring Speed - Adenia, Atika Putri; Jayanudin, Jayanudin; Kosimaningrum, Widya Ernayati; Kurniawan, Teguh; Zulfaidah, Farah Alifia; Siahaan, Yudhistira Madani Putra (Metalurgi, 2024)
Indonesia is the world’s second-largest tin exporter; however, downstream utilization of tin remains limited. One potential source of secondary tin is the by-product generated from the production of DMT (dimethyltin dichloride) at PT Timah Industri, which contains 40–70% tin in both organic and inorganic forms. This study aims to investigate the extraction kinetics and evaluate the effects of solvent type and agitation speed on tin recovery from the DMT by-product. Extraction experiments were conducted using different solvents (water, 50% methanol, and pure methanol) and agitation speeds (300 and 400 rpm) for 24 hours. Tin concentrations in the filtrate were determined using XRF (x-ray fluorescence). Kinetic modeling was performed using first-order and second-order models through both linear and non-linear approaches. The results show that the extraction process follows second-order kinetics, with rate constants (k) in the short-time regime ranging from 0.002 to 0.005 L·(g·min)⁻¹ and in the long-time regime from 0.0001 to 0.0002 L·(g·min)⁻¹. Water demonstrated the highest dissolution capacity (35.35 ± 0.09%), while pure methanol selectively dissolved organotin compounds (30.45 ± 0.12%). The 50% methanol solvent yielded intermediate extraction results (32.65 ± 0.37%) due to the combined characteristics of both solvents. Agitation speed significantly enhanced tin dissolution.